An experimental and numerical scrutiny of crashworthiness variables for square column with V-notch and groove initiators under quasi-static loading. Issue 1 (1st January 2017) - Balaji, G.; Annamalai, K.
Abstract: Crashworthiness parameters like internal energy absorption and crush force efficiency are the key constants in evaluating the component crashworthiness and its safety. In the design of automotive structures for crashworthiness, there is an immense requirement for null strain submodules that provide a rigid room of survival area for the occupants and deformable submodules which can dematerialize the kinetic energy effectively. The front crash box of an automotive car is one of the most important deformable components which dissipate kinetic energy while frontal crash, which is the most persistent crash situation affects the entire automotive structural behavior. In this research, quasi-static axial loading response and crashworthiness characteristics of empty hollow tube, empty hollow tube with V-notch and empty hollow tube with horizontal groove have been investigated through experimental and numerical simulations. The axial quasi-static loading was executed at a couple of feed rates to evaluate the crashworthiness constants of each sample against quasi-static loading. The supremacy of feed rate, V-notch and square grooves over empty hallow structures were pursued. The numerical simulation of quasi-static test was performed in accordance with explicit finite element algorithm of PAMCRASH in order to envisage and justify the crashworthiness of each variety of specimen with experimental results. The derived crashworthiness experimental results and deformation behaviours of finite element analysis are found to be in a good concurrence with the experimental results.